EVALUATING THE EFFECTIVE FACTORS IN PROMOTING THE TARGET AUDIENCE-BASED ATTRACTION OF A MUSEUM WITH THE APPROACH OF INCREASING SOCIAL INTERACTIONS (CASE STUDY: STUDY OF TEHRAN CITY REGION 2, IRAN) - Afshin Ghorbani Param; Abel Minasians; Fatemeh Abasi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
As a place for social relations, museums can be effective in sociability, increasing social interactions, and creating vitality. The society can create a dynamic, lively and active atmosphere in the museum as a public place. In this essay, the parameters affecting the architectural design of museums to increase audience attention were studied by investigating the factors influencing social interactions in museums and the impact of some human-physical parameters. The research methodology consisted of hypothesis testing and a case study of public places of museums, which was investigated through a survey and a questionnaire. Correlation analysis was applied to the collected data via SPSS statistical software and meaningful relationships between variables affecting sociability were concluded. The results revealed that the sociability of the architecture of public places is achieved by the association of their physical, spatial elements and the social-psychological factors of their audience